2018
DOI: 10.7567/jjap.57.096203
|View full text |Cite
|
Sign up to set email alerts
|

Chemical reaction process for magnetite nanoparticle synthesis by atmospheric-pressure DC glow-discharge electrolysis

Abstract: We investigated the reaction process in magnetite nanoparticle (MNP) synthesis by glow-discharge electrolysis in atmospheric air combined with iron electrolysis using NaCl aqueous solution as electrolyte. The iron electrolysis supplies Fe2+ in the solution, and electrons from the glow discharge induce liquid-phase reactions. We found experimentally that the concentration of dissolved oxygen (DO) in the solution is a key parameter in MNP synthesis. The excess oxidation of ferrous iron species at a high DO conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In general, dissolved oxygen (DO) affects chemical reactions in the solution. For example, Yamazaki and coworkers have reported that the DO concentration is a key parameter in the synthesis of magnetite nanoparticle by glow-discharge electrolysis [43]. The concentration of DO significantly determines the kind of the final product, nonmagnetic hematite (Fe 2 O 3 ) nanoparticles or ferromagnetic magnetite (Fe 3 O 4 ) nanoparticles.…”
Section: Effect Of Dissolved Oxygenmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, dissolved oxygen (DO) affects chemical reactions in the solution. For example, Yamazaki and coworkers have reported that the DO concentration is a key parameter in the synthesis of magnetite nanoparticle by glow-discharge electrolysis [43]. The concentration of DO significantly determines the kind of the final product, nonmagnetic hematite (Fe 2 O 3 ) nanoparticles or ferromagnetic magnetite (Fe 3 O 4 ) nanoparticles.…”
Section: Effect Of Dissolved Oxygenmentioning
confidence: 99%
“…Consequently, the plasma-liquid interface as well as the bulk liquid becomes the reaction zone for many specific physical and chemical processes. Numerous researches report that this reaction zone can be used for synthesizing novel nanomaterials such as noble metals [33][34][35][36][37][38][39], magnetic materials [40][41][42][43], and alloys [44][45][46] in suitable conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In previous papers, we reported several types of atmospheric-pressure glow discharges using liquid electrolyte electrodes and helium flow [27][28][29][30][31][32][33][34][35][36][37]. We showed that the optical emission of Na was observed from the plasma when a NaCl solution worked as the cathode of the discharge [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 98%
“…The difference between the plasma-assisted and conventional electrolyses is summarized as follows; 1) the plasma-assisted electrolysis can utilize the interface between gas (plasma) and solution for redox reactions [2, 3], 2) electrons can have kinetic energy if the plasma works as the cathode [4-7], and 3) ions and neutral radicals are transported from the plasma in addition to electrons [8][9][10]. We can obtain various nanoparticles of metals [11][12][13][14] and oxides [15][16][17] in a form of suspension by plasma-assisted electrolysis. The synthesis of nanoparticles is owing to the reduction of metal cations by the reaction with electrons, but the contribution of atomic…”
mentioning
confidence: 99%